The role of immunoglobulin E in non-atopic disorders - Thaçi, Kujtim; Gyorgypal, Aron; Anthony, Robert M.; Conroy, Michelle E. (Frontiers in Immunology, 2026)
Immunoglobulin E (IgE) and its corresponding Fc epsilon receptors (FcϵRs) are essential components of the immune system. The constant, crystallizable fragment (Fc) region of IgE binds with high affinity to its specific receptor, FcϵRI, anchoring IgE molecules to the surface of effector cells such as mast cells and basophils. Once bound, IgE uses its antigen-binding fragment (Fab) to recognize specific antigens. Antigen-induced crosslinking of cell-bound IgE triggers activation of these effector cells. Over fifty years ago, intensive research identified IgE as a key mediator of allergic reactions. Subsequent studies have demonstrated that the production of antigen-specific IgE and its interactions with innate immune cells are critical not only for allergic responses but also for certain non-atopic immune processes. N-glycosylation, a crucial post-translational modification, has been shown to strongly influence the stability and function of IgG antibodies. Similarly, glycosylation is vital for maintaining the structure and biological activity of IgE. Individual variations in IgE glycosylation patterns regulate its functional properties, contributing to the diversity and complexity of IgE-mediated immune responses. Given the emerging role of IgE in non-atopic diseases, understanding how site-specific glycosylation variations affect IgE function is essential for characterizing disease-specific molecular signatures and identifying new therapeutic targets. Comprehensive glycoproteomic analyses of IgE from diverse pathological conditions may clarify how glycosylation influences disease progression, identify Fc glycans associated with pathology, and elucidate their biological roles.